Perfil epidemiológico y características clínicas de la onicomicosis en población militar - Casanova-Claure, Eliana (2017)
ABSTRACT Onychomycosis is a frequent nail infection. It is a public health problem due to its high morbidity rate. In the military, it is related to their working conditions. Objective: To know the prevalence, clinical characteristics and etiological agents of onychomycosis pedis in the military population. Material and methods: Descriptive, retrospective, cross-sectional, non-experimental study. Sixty-seven people participated, including officers, technicians, non-commissioned officers and troop personnel; the cases were treated in the dermatology service of a military hospital between February 2016 and February 2017. Results: 50.7% of the population were under 60 years old, 7.5% female and 65.7% belonged to the group of technicians and non-commissioned officers; 80.6% had involvement of two nails, 50.7% of three nails and 3% of 10 nails. In 62.7% of the cases, the clinical form that prevailed was lateral distal subungual onychomycosis. In 41.8% we found positivity in the direct test to hyphae, 32.8% to yeast, 10.4% to mixed species. In 50.7%, the culture was positive to Trichophyton rubrum, 23.9% to Candida parapsilosis and 4.5% to mixed infections. Conclusions: In the military population, the prevalent etiological agent of onychomycosis pedis was Trichophyton rubrum; the clinical form was subungual distal onychomycosis; it predominated in males and in the group of technicians and non-commissioned officers.